Po akcji „Wisła”. Ewolucja polityki państwa polskiego wobec ludności ukraińskiej w latach 1947-1958 - Olejnik, Leszek (Acta Universitatis Lodziensis. Folia Historica, 2001)
The underground structures of the Ukrainian nationalists in Poland were crushed as a result of the „Vistula” action which was carried out in 1947. Simultaneously over 140 thousands of Ukrainian people were expelled from the south-east part of Poland and dispersed on the west and north territory. During the following years the Ukrainian problem still absorbed the attention of the party and state governors, especially in a connection with the vivid tendencies of the deportees to return to their former places of settlement. In April 1952 Political Office of the Central Committee of the Polish United Workers’ Party (KC PZPR) adopted a secret decision on the Ukrainian question. That act started the process o f changes in the attitude towards the Ukrainian minority in Poland. The results of the evolution of that policy were showed more clearly simultaneously to the increase of the political liberalisation in the country since 1955. In 1956 among the others the Ukrainian Socio-Cultural Association was created and the Ukrainian magazine „Nasze Slowo” started to be published. Even greater results were achieved in the fields of the cultural and educational life of that community and the considerable economic assistance was given to the Ukrainians as well. Still their most important claims (- the condemnation of the „Vistula” action and closely connected with that - a permission for the mass return to the former territory of their settlement) for various reasons were not fulfilled. This community obtained a formal equality of rights with the other ethnic groups. Still its situation was deeply influenced by the consequences of the decision which had been took up in 1947. A dispersion of the Ukrainians people limited the possibilities of the wider development of their cultural and religious life as well as their education.